Cefotaxime Induced Staphylococcal Scalded Skin Syndrome: A Case Report - Jakkula, Shirisha; Chinnala, Satish; Komuravelly, Shravani; Eggadi, Venkateshwarlu (Journal of Pharmacy Practice and Community Medicine)
Staphylococcal Scalded Skin Syndrome (SSSS) is as well called as Ritter von Ritterschein disease, Lyell disease, Ritter disease and staphylococcal necrolysis of the epidermis. More common in neonates and children of age less than five years and are at a greater risk of SSSS. To fight against SSSS, children should attain lifetime immunity in the form of antibodies against exotoxins of staphylococcal strains. Symptoms include fever and redness on the overall surface of skin. Within 24-48h, fluid-filled blisters appear on the body. We report a case of 2-year-old male child developed SSSS after intravenous administration of Cefotaxime.
Keywords: Staphylococcal scalded skin syndrome; Immunity; Exotoxins; Cefotaxime; Exfoliative; Cephalosporins.